LINGUISTIC SHIFT AMONG GEN Z IN COMPUTER-MEDIATED COMMUNICATION - Conny, Conny; Yultisa, Nudia; Sagala, Rakhmat Wahyudin; Rezeki, Tri Indah (English Review: Journal of English Education, 2024)
In the quickly changing context of the Information and Communication Technology (ICT) revolution, it is essential to comprehend how Generation Z (Gen Z) modifies their language usage. As digital natives who have grown up with technology, Gen Z is at the forefront of shaping and transforming language in the digital age. This study investigates the notable changes in Gen Z's language use in digital discourse, emphasizing Instagram. The goal is to recognize how the linguistic shifts of Gen Z are changing how people communicate in digital environments. This study used a qualitative content analysis method to analyze the data from Instagram comments and posts, highlighting essential features such mixing language, new slang and expression, use of non-standard spelling, emoji language and use of symbols, and contextualization in pop culture and social media trends. The results show that Gen Z used the linguistic shift in their communication in digital discourse such as communication in Instragram. These linguistic patterns show how Gen Z navigates and shapes their digital identities through language and how engaged they are with pop culture and social media trends. This study adds to our understanding of how digital platforms shape language use and social interaction in the modern period. It emphasizes the necessity of more investigation into how these changes may affect sociolinguistic theory, pedagogy, and communication techniques.